Analisis Pembangunan Ekonomi Kapitalis Dalam Film Berjudul “Wolf Of Wall Street” - Agastya Bhima Kumara Dewa; Hifdhul Haqqi Nazili Rohman (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research focuses on the mechanisms of the world system which is characterized by the dominances of capitalism practices, an economic mechanisms with capital as the main thing in the process. The circulation of capital is forbid to stop, because it would be caused an economic disaster on a global scale. In the global hierarchy, world systems theory divides the world into two groups of countries. Groups of developed and groups of developing countries. Determining the most ideal thing to manage the economic process towards sustainable development. Through descriptive qualitative research methods, it is hoped that we can project the social setting of research that will be used to formulate answers about ideal strategies for developing countries to face capitalism as a world system. One way is by increasing local productivity. In an effort to increase productivity, of course the quality of human resources are needed, along with a bureaucracy that is free from corrupt practices. The realization of sustainable development will constructs a way for developing countries to empower their existence against the domination of developed countries.